Commentary: What, exactly, is 'online' education? - Nichols, Mark (Journal of Learning for Development, 2023)
As responsible educators, it is time we admitted that we do not know what 'online' education is. We also need to confront the discomforting realisation that no one else does, either. The term 'online' has reached the stage where it is now so inclusive as to be meaningless. In embracing too much, it describes nothing. What was once a useful term to describe using the internet as part of asynchronous distance education is now used universally, to describe almost anything. Lectured, synchronous classes are now 'online' (Johnson et al., 2022). Emergency remote teaching and learning during the Covid-19 pandemic was 'online'. Including additional resources on an LMS for students to refer to after class is considered ‘online’. Across much of the educational spectrum, to be 'online' now is far from unusual. In this commentary I make the case that the term 'online' needs a forced retirement, or, at the least, additional context when it is applied.